The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.2113/2022/3810988
|View full text |Cite
|
Sign up to set email alerts
|

Research on Theory and Technology of Floor Heave Control in Semicoal Rock Roadway: Taking Longhu Coal Mine in Qitaihe Mining Area as an Example

Abstract: As one of the most common disasters in deep mine roadway, floor heave has caused serious obstacles to mine transportation and normal production activities. The third section winch roadway in the third mining area of Qitaihe Longhu coal mine has a serious floor heave due to the large buried depths of the roadway and the semicoal rock roadway, and the maximum floor heave is 750 mm. For the problem of floor stability, this paper establishes a mechanical model to analyze the stability of roadway floor heave by ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…However, numerous scholars have found that this effective stress fails to respond to changes in the pore structure within the fractured body [ 36 , 37 ]. Therefore, a correction for Terzaghi’s equation is needed in rock percolation scenarios; Biot [ 38 , 39 ] et al proposed an effective stress equation that considers the effect of the pore structure of the rock body: where α is the Biot coefficient (this is interchangeable with porosity ϕ).…”
Section: Resultsmentioning
confidence: 99%
“…However, numerous scholars have found that this effective stress fails to respond to changes in the pore structure within the fractured body [ 36 , 37 ]. Therefore, a correction for Terzaghi’s equation is needed in rock percolation scenarios; Biot [ 38 , 39 ] et al proposed an effective stress equation that considers the effect of the pore structure of the rock body: where α is the Biot coefficient (this is interchangeable with porosity ϕ).…”
Section: Resultsmentioning
confidence: 99%
“…CBM is gradually formed in the long-term complex geological evolution process (Wang and Du, 2020;Zhou et al, 2021), so its occurrence is affected by structural evolution, depositional environment, buried depth, roof and floor lithology, coal seam thickness, hydrogeology, and magmatic activity (Xie et al, 2018;Zou et al, 2018a;Zhang C. L. et al, 2020;Kong B. et al, 2021;Zhang C. L. et al, 2021). Tectonic evolution is the key factor controlling the generation, migration, and occurrence of CBM (Zou et al, 2018b;Zhang K. Z. et al, 2020;Zhou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, China has made many top coal mining research achievements. Other researchers have also studied in this field in different ways (S Bai and H Tu, 2020;Zhou et al, 2022;Zhang et al, 2020;Zhang and Zhang, 2019;Xie and Zhou, 2008) . In general, the research and application of thick coal seam mining technology in China is at the world's leading level.…”
Section: Introductionmentioning
confidence: 99%